PENGARUH PETA KONSEP PADA KEMAMPUAN MENULIS SISWA KELAS 7 SMPN 14 PEKANBARU DALAM MENULIS TEKS DESKRIPTIF - Na’wa Agustina Putri Setiawan; Hadriana '; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to find out whether there is a significant effect of concept mapping on the students’ ability of SMPN 14 Pekanbaru in writing descriptive texts. This is a pre-experimental research with one group pre-test post-test design. In conducting this research, a single group was selected to be a sample by using cluster random sampling. There were 36 students as the sample. A writing test was used both in pre and post-test. In order to know the difference between pre-test and post-test and to analyze the hypotheses, t-test formula was used. After analyzing the data, it was found that t-test score was 7.779 while t-table score in significance level 5% df= 34 was 2.032. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted. It can be further understood that “there is a significant effect of concept mapping on the students’ ability of SMPN 14 Pekanbaru in writing descriptive texts”. Based on the research findings, it is suggested that concept mapping can help the students to improve their writing ability especially in writing descriptive text.Key Words: Effect, Concept Mapping, Writing Ability, Descriptive Text